Responding to Crises: The Problematic Relationship between Security and Justice in The Responsibility to Protect. Issue 3 (19th June 2013) - Bohm, Alexandra
Abstract The Responsibility to Protect (RtP) report has been hailed by academics and policy makers alike as an important policy development in the international community's potential to protect vulnerable and insecure populations from violence. This article critically assesses the RtP, examining the problems with its particular conception of justice and security based on the nature and source of threats to individuals. It criticises the RtP's focus on crises, arguing that this downplays the importance of systemic, 'chronic' problems of injustice and disorder across the globe – and thus the importance of responding to these chronic problems. This emphasis, together with the RtP's focus on civil and political rights over socioeconomic rights, results in the causes of crises being perceived as local, thereby obviating the need to admit the role of the international community in contributing to current crises and systemic injustices. Based on these criticisms, this article concludes that the RtP's narrow conception of the relationship between justice and security will not further the international community's ability to discharge its responsibility towards individuals across the globe.